A green paradise. Economic strategies, collective practices, and local ancestors of the Iron Age community of Masāfī (Emirate of Fujairah, UAE) - Benoist, Anne (Proceedings of the Seminar for Arabian Studies, 2013)
Excavations in Masāfī (Emirate of Fujairah, UAE) have revealed several constructions belonging to an Iron Age settlement. Research carried out in 2011 has demonstrated that an area of irrigated cultivation was located in the centre of the Iron Age territory. It was bordered to the south-east by a public place, including a succession of communal buildings, an open air market, a temple, and a circular area including a podium and to the north-west by a fortified settlement. The latter was organized in two parts: a high place of collective and probably defensive use, almost entirely destroyed, and a lower place that included private houses. Results of recent excavations in these two areas are presented in this article, as well as a late Bronze Age settlement newly discovered to the south-west.